Is irrigation fit for purpose? A review of the relationships between scheme size and performance of irrigation systems - McCarthy, Nancy; Ringler, Claudia; Agbonlahor, Mure Uhunamure; Pandya, A. B.; Iyob, Biniam; Pérez, Nicostrato D. (International Food Policy Research Institute, 2023)
Irrigation is increasingly being called upon to help stabilize and grow food and water security in the face of multiple crises; these crises include climate change, but also recent global food and energy price crises, including the 2007/08 food and energy price crises, and the more recent crises triggered by the COVID 19 pandemic and the war on Ukraine. While irrigation development used to focus on public, large-scale, surface- and reservoir-fed systems, over the last several decades, private small-scale investments in groundwater irrigation have grown in importance and are expected to see rapid future growth, particularly in connection with solar-powered pumping systems. But is irrigation ‘fit-for-purpose’ to support population growth, economic development, and multiple food, energy and climate crises? This paper reviews how fit-for-purpose irrigation is with a focus on economies of scale of surface and groundwater systems, and a particular examination of systems in Sub-Saharan Africa where the need for expansion is largest. The review finds challenges for both larger surface and smaller groundwater systems in the face of growing demand for irrigated agriculture and dwindling and less reliable water supplies. To support resilience of the sector, we propose both a holistic design and management improvement agenda for larger surface systems, and a series of suggestions to improve sustainability concerns of groundwater systems